Garbage Management Training for Women and Teacher in the Bureau of Logistics Office Medan North Sumatera - Rahmawaty; Rauf, Abdul; Astuti, Widya (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
The problem of garbage in Medan City is one of the problems that needs to be addressed immediately. The program of community service activities aims to provide training to the community on how to process garbage into something useful. This Community Service was conducted for women and teachers in Bureau of Logistics (Bulog) Foundation teachers with presentation, discussion and garbage management practices. Presentation activities carried out by the community service team by providing material on how to process household organic garbage into compost in the Bulog Office Hall, Medan. After finishing the presentation of the material, participants were given the opportunity to discuss about the material provided to the questions and answers or responses. After the presentation and discussion, follow the training on how to make compost from household organic garbage in Sei Semayang Village, Deli Serdang Regency. The positive responses were received with a good reception at the arrival of the community service team at the location and at the time the presentation and training were conducted. This activity was successfully carried out with the support of woman and Bulog foundation teachers.